The elements of classroom physical environment that affect the learning process of English as a Foreign Language of 2nd Baccalaureate students from Colegio Fiscal Mixto Ismael Pérez Pazmiño. - Lorentzen Moreira, Maria Gabriela (2019)
Classroom physical design plays an important role in the academic achievement of students. For them, the classroom is not only a scholarly space, but also a physical, emotional and social setting. The objective of this study is to analyze how the physical environment affects the EFL learning process of students from “Ismael Pérez Pazmiño”. The research approach used to endorse this study was a descriptive research. Two groups of students are observed during this research study: students from 2nd National Baccalaureate and students from 2nd International Baccalaureate, both assigned to study under 2 different classroom environments. The International Baccalaureate group consists of 19 students who study in well-renovated classrooms; while the National Baccalaureate group includes 56 students who study in non-renovated classrooms. A survey was administered to both groups of students using Likert Type Scales to analyze how the physical environment perceived by them is. To reinforce this theory, the scores in the final English exam of the second five-month period for the two groups are compared to examine the physical environmental effect of the classroom on student academic achievement. These scores are tabulated and examined using descriptive statistics. The results show that there are meaningful differences between the achievements of the students from International Baccalaureate and the students from National Baccalaureate in English in favor of the International Baccalaureate group who have studied under positive classroom conditions. The researcher has also surveyed the teachers’ point of view regarding the learning environment and its potential impact on students’ academic achievement in English.